A method for sterilizing by combining lauroyl arginine ethyl ester hydrochloride antibacterial nanofiber membrane with ultrahigh pressure
Through the combined antibacterial nanofiber membrane of lauroyl arginine ethyl hydrochloride combined with ultra-high pressure sterilization, the problems of low efficiency and sublethal damage in ultra-high pressure processing technology are solved, and efficient food sterilization and food safety are achieved. Extends the shelf life of food and saves energy.
Patent Information
- Application Number
- CN202111580045.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-22
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-12-22
AI Technical Summary
Ultra-high pressure processing technology has problems of low efficiency and sublethal damage to microorganisms during the sterilization process, which affects food safety and processing efficiency.
The PLA/LAE nanofiber membrane was prepared by electrospinning technology by using the combined sterilization method of lauroyl arginine ethyl ester hydrochloride antibacterial nanofiber membrane and ultra-high pressure, and mixed with the sample to be sterilized under ultra-high pressure of 200-300MPa Perform processing to reduce high-pressure processing strength and improve sterilization efficiency.
It significantly improves the ultra-high pressure sterilization efficiency, reduces sublethal damage to microorganisms, extends the storage period of low-acid foods, saves energy, and reduces the loss of high-pressure equipment.
Smart Images

Figure BDA0003425777790000041 
Figure BDA0003425777790000042 
Figure BDA0003425777790000043
Abstract
Description
Technical Field
[0001] The invention belongs to the field of food sterilization, and specifically relates to a method for sterilizing by combining lauroyl arginine ethyl ester hydrochloride antibacterial nanofiber membrane with ultrahigh pressure. Background Art
[0002] In recent years, consumers' pursuit of natural and nutritious food has made "minimum processing" a trend in the development of the industry. As the most commercialized non-thermal processing technology, high pressure processing (HPP) has attracted widespread attention because it can effectively kill spoilage and pathogenic microorganisms while retaining the sensory and nutritional quality of food. However, researchers have found that the HPP sterilization curve is often "two-stage" or "tailing", which reduces the HPP sterilization efficiency. In addition, the sublethal damage to microorganisms caused by HPP treatment can easily lead to an overestimation of the sterilization effect, thereby affecting the assessment of food safety.
[0003] The barrier technology effectively improves the HPP sterilization efficiency while reducing the processing intensity of HPP in an economical and reasonable way. Studies have found that when two sterilization methods with the same action site work together, one treatment method will inevitably increase the sensitivity of microorganisms to the other treatment method. It is generally believed that the cell membrane is the main action site of HPP, and LAE mainly binds to the cell membrane through electrostatic interaction, resulting in changes in cell membrane permeability, outflow of contents, and then cell death. Therefore, there may be a certain synergistic sterilization effect between the two. However, when antimicrobial agents are directly added to the food system, they are very likely to interact with food components and lead to a decrease in antibacterial activity. Antimicrobial packaging can slowly release active substances into food to inhibit the growth of microorganisms, which can solve this problem well. Compared with traditional film making technology, electrospinning fiber membrane can be prepared at room temperature and has a large specific surface area. It is a good carrier of active substances and is expected to be used as a barrier technology to improve the sterilization efficiency of HPP. Summary of the invention
[0004] The invention aims to provide a method for sterilizing by combining lauroyl arginine ethyl hydrochloride antibacterial nanofiber membrane (polylactic acid / lauroyl arginine ethyl hydrochloride nanofiber membrane, i.e. PLA / LAE nanofiber membrane) with ultrahigh pressure.
[0005] The method for sterilizing by combining lauroyl arginine ethyl ester hydrochloride antibacterial nanofiber membrane and ultrahigh pressure provided by the present invention comprises the following steps: mixing the lauroyl arginine ethyl ester hydrochloride antibacterial nanofiber membrane with a sample to be sterilized, and then subjecting the mixture to pressure treatment at 200-300 MPa for 5 minutes at room temperature.
[0006] In the above method, the lauroyl arginine ethyl ester hydrochloride antibacterial nanofiber membrane and the sample to be sterilized can be mixed in a ratio of 3:5 (S / V, surface area / volume).
[0007] Before use, the lauroyl arginine ethyl ester hydrochloride antibacterial nanofiber membrane needs to be placed in a sterile sampling bag and irradiated under an ultraviolet lamp (eg, for 2 hours) for sterilization.
[0008] The lauroyl arginine ethyl ester hydrochloride antibacterial nanofiber membrane can be cut into suitable specifications as needed, such as 1 cm×3 cm small pieces.
[0009] According to one embodiment of the present invention, the lauroyl arginine ethyl ester hydrochloride antibacterial nanofiber membrane and the sample to be sterilized can be mixed in a high-temperature cooking bag, and after mixing, the bag is heat-sealed after the top air is removed.
[0010] The pressure-maintaining treatment at 200-300 MPa for 5 minutes can be performed by using FB-110G5 high-pressure equipment with water as the pressure transmission medium to perform the pressure-maintaining treatment on the sample.
[0011] The lauroyl arginine ethyl ester hydrochloride antibacterial nanofiber membrane described in the present invention is prepared according to a method comprising the following steps:
[0012] 1) dissolving lauroyl arginine ethyl ester hydrochloride (LAE) powder in N,N-dimethylformamide (DMF), mixing it with chloroform in a ratio of 1:9 (v / v), adding polylactic acid masterbatch, stirring at room temperature until completely dissolved, preparing a spinning solution with a LAE mass concentration of 0.5%-2.0%, and ultrasonically degassing for standby use;
[0013] 2) The degassed spinning solution is subjected to electrostatic spinning to obtain an electrostatically spun nanofiber membrane, which is then placed in a vacuum drying oven for drying to completely volatilize the residual solvent, thereby obtaining the lauroyl arginine ethyl ester hydrochloride antibacterial nanofiber membrane.
[0014] In step 1) of the above method, the mass concentration of the polylactic acid masterbatch in the spinning solution may be 6%-10%, preferably 8%.
[0015] In step 1) of the above method, the mass concentration of LAE in the spinning solution may specifically be 0.5%, 1.0%, 1.5% or 2.0%.
[0016] In step 2) of the above method, the process conditions of the electrospinning are as follows: adjusting the distance between the needle and the drum to 15 cm, setting the voltage to 10-16 kV, and the spinning solution flow rate to 0.6-1.0 mL / h; the preferred conditions are: adjusting the distance between the needle and the drum to 15 cm, setting the voltage to 14 kV, and the spinning solution flow rate to 0.8 mL / h.
[0017] Furthermore, the specific method of the above step 2) is as follows:
[0018] The degassed spinning solution was transferred to a 10mL needle tube, and a flat-head needle with an inner diameter of 0.40mm was used as the capillary for electrospinning. After the bubbles in the needle tube were exhausted, it was fixed horizontally on the slide, so that its axis was consistent with the center of the spinning receiving device, and the distance between the needle and the drum was adjusted to 15cm, the voltage was set to 14kV, the spinning solution flow rate was 0.8mL / h, and the drum with aluminum foil was used as the receiving device to prepare the electrospun fiber membrane. After that, the prepared electrospun nanofiber membrane was placed in a vacuum drying oven for 24h to completely evaporate the residual solvent.
[0019] The above-mentioned lauroyl arginine ethyl ester hydrochloride antibacterial nanofiber membrane also belongs to the protection scope of the present invention.
[0020] The sample to be sterilized in the present invention is a liquid sample, specifically a food or beverage (such as coconut water, fruit and vegetable juice, etc.); it is particularly suitable for low-acid food or beverage.
[0021] The combined sterilization method of the present invention can kill Gram-positive bacteria (such as Staphylococcus aureus) and Gram-negative bacteria (such as Escherichia coli O157:H7).
[0022] The present invention adopts electrospinning technology to prepare an active nanofiber membrane with biodegradable material PLA as the substrate and LAE as the antibacterial agent, and uses it as a fence technology to reduce the ultra-high pressure processing intensity and maintain the storage stability of low-acid ultra-high pressure food, so as to reduce the high-pressure processing intensity, save energy and ensure the safety of HPP food.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The present invention utilizes electrospinning technology to prepare a PLA / LAE antibacterial fiber membrane with a fiber diameter of 325-364 nm, which has a high specific surface area, can effectively inhibit common pathogenic microorganisms, and has good antibacterial activity.
[0025] (2) PLA / LAE antimicrobial film is used as a barrier technology to assist ultrahigh pressure sterilization, which improves the efficiency of ultrahigh pressure sterilization and significantly reduces the sublethal damage of microorganisms during high pressure processing, greatly improving the safety and storage stability of ultrahigh pressure food. It is applied to the processing of low-acid coconut water, which can reduce the ultrahigh pressure processing intensity from 500MPa / 5min to 300MPa / 5min, and enable coconut water to be stored at 4℃ for more than 49 days, thus extending the shelf life of low-acid food, greatly saving energy and reducing the loss of ultrahigh pressure equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The effect of different LAE contents on the microstructure of PLA nanofiber membranes. A. 0% LAE; B. 0.5% LAE; C. 1.0% LAE; D. 1.5% LAE; E. 2.0% LAE; F. Average diameter of nanofiber membranes with different LAE contents.
[0027] Figure 2 Infrared spectra of LAE powder and LAE / PLA nanofiber membranes with different contents.
[0028] Figure 3 (A) Thermogravimetric analysis and (B) differential thermogravimetric curves of PLA and PLA / LAE electrospun films; the concentration of LAE in A is from low to high as indicated by the arrow; the concentration of LAE in B is from low to high as indicated by the arrow.
[0029] Figure 4 The inhibition zones of PLA / LAE antibacterial films (A) S. aureus and (B) E. coli O157:H7, where the LAE contents are: (a) 0% LAE; (b) 0.5% LAE; (c) 1.0% LAE; (d) 1.5% LAE; (e) 2.0% LAE.
[0030] Figure 5 The killing effect of PLA / LAE nanofiber membrane on S.aureus and E.coli O157:H7.
[0031] Figure 6 The killing effect of the combined action of ultrahigh pressure and antibacterial film on (A) S. aureus and (B) E. coli O157:H7; wherein, in A, the pressure of the curve corresponding to the arrow points is from low to high; in B, the pressure of the curve corresponding to the arrow points is from low to high.
[0032] Figure 7 The effect of ultrahigh pressure combined with antibacterial film on sublethal cell damage, that is, the growth of (AD) S. aureus and (EG) E. coli O157:H7 on selective medium (gray) and non-selective medium (black) under different treatments. A and E are 0.1MPa; B is 100MPa; C and F are 200MPa; D and G are 300MPa.
[0033] Figure 8 This is the effect of the time sequence of high pressure and film application on the killing effect of S. aureus.
[0034] Fig. 9Figure 2 shows the growth curve of (A) total colony count and (B) mold and yeast in coconut water. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with specific examples, but the present invention is not limited to the following examples. The methods described are conventional methods unless otherwise specified. The raw materials described can be obtained from public commercial channels unless otherwise specified.
[0036] Example 1: Polylactic acid electrospinning
[0037] 1. Test methods
[0038] 1.1 PLA spinning solution preparation
[0039] Chloroform and DMF were mixed in a volume ratio of 9:1 to form a mixed solvent system for the preparation of polymer solution. 1.20, 1.60, and 2.00 g of PLA masterbatch (molecular weight 50 kDa) were weighed respectively, and 20 mL of the mixed solution of chloroform and DMF was added. Electromagnetic stirring was performed at room temperature for 8 h until completely dissolved, and spinning solutions with polymer concentrations of 6%, 8%, and 10% were prepared. After ultrasonic degassing for 2 h, the spinning solutions were used.
[0040] 1.2 Preparation of PLA nanofiber membrane
[0041] The degassed spinning solution was transferred to a 10 mL screw-mouth needle tube, and a flat-head needle with an inner diameter of 0.40 mm was used as a capillary to discharge the bubbles in the needle tube. It was then fixed horizontally on a slide so that the axis of the needle tube was consistent with the center of the spinning receiving device, and the distance between the needle and the drum was adjusted to 15 cm. The polymer concentration was set to 6%, 8% and 10%, respectively, the spinning voltage was 10 kV, 12 kV, 14 kV, 16 kV, the flow rate was 0.6 mL / h, 0.8 mL / h, 1.0 mL / h, and the single factor test method was used to prepare the electrospun fiber membrane. In order to completely evaporate the solvent, the prepared electrospun nanofiber membrane was placed in a vacuum drying oven and dried for 24 hours.
[0042] 1.3 Scanning electron microscopy (SEM) characterization
[0043] The microscopic morphology of electrospun nanofibers was observed using a field emission scanning electron microscope (FESEM) at an accelerating voltage of 20 kV. Before the experiment, a 5 mm × 5 mm sample was fixed on a metal sample stage with conductive glue and observed after gold spraying. The diameters of 40 fibers were randomly measured from the SEM image using Nano Measure software to analyze the diameter and uniformity of the nanofibers.
[0044] 1.4 Statistical analysis
[0045] SPSS18.0 was used for one-way analysis of variance and Duncan multiple comparisons, with a significance level of p < 0.05. All test results are expressed as "mean ± standard deviation".
[0046] 2. Results and Discussion
[0047] 2.1 Effect of solute mass fraction on nanofiber morphology
[0048] In order to investigate the effect of different PLA concentrations on the morphology of nanofibers, the spinning voltage was set to 14 kV, the flow rate was set to 0.8 mL / h, and the receiving distance was set to 15 cm. Nanofibers were prepared using PLA solutions of different concentrations. The results are shown in Table 1.
[0049] Table 1 Effect of different PLA concentrations on nanofiber diameter distribution
[0050]
[0051] Note: Different lowercase letters in the same column indicate significant differences among samples (p<0.05).
[0052] 2.2 Effect of spinning voltage on nanofiber morphology
[0053] Using 8% PLA solution as the spinning solution, the flow rate was set to 0.8 mL / h, the receiving distance was 15 cm, and the electrospinning fiber membrane was prepared at 10 kV, 12 kV, 14 kV, and 16 kV, respectively. The results are shown in Table 2.
[0054] Table 2 Effect of different spinning voltages on nanofiber diameter distribution
[0055]
[0056] Note: Different lowercase letters in the same column indicate significant differences among samples (p<0.05).
[0057] 2.3.3 Effect of spinning flow rate on nanofiber morphology
[0058] In order to explore the effect of spinning flow rate on fiber morphology, the spinning voltage was set to 14 kV, the spinning distance was set to 15 cm, 8% PLA was used as the spinning solution, and nanofiber membranes were prepared at different propulsion speeds. The results are shown in Table 2.
[0059] Table 3 Effect of different spinning flow rates on nanofiber diameter distribution
[0060]
[0061] Note: Different lowercase letters in the same column indicate significant differences among samples (p<0.05).
[0062] The effects of polymer concentration, spinning voltage and flow rate on nanofiber formation were analyzed by single factor experiments, and the optimal process conditions were screened based on fiber diameter and uniformity. The results showed that when the spinning distance was 15 cm, the PLA mass fraction was adjusted to 8%, the spinning voltage was 14 kV, and the flow rate was 0.8 mL / h, continuous, uniform and bead-free nanofibers could be prepared, with an average diameter of 634 nm and a coefficient of variation of only 20.89%, showing good spinnability.
[0063] Example 2: Preparation and performance characterization of PLA / LAE antibacterial film
[0064] 1. Test methods
[0065] 1.1 Preparation of electrospun fibers
[0066] A certain mass of lauroyl arginine ethyl ester hydrochloride (LAE) powder was weighed and dissolved in 2 mL of DMF, and then mixed with 18 mL of chloroform in a ratio of 1:9 (v / v), and then 1.60 g of polylactic acid masterbatch (molecular weight 50 kDa) was added. The mixture was electromagnetically stirred at room temperature for 8 h until completely dissolved, and film-forming solutions with LAE concentrations of 0.5%, 1.0%, 1.5% and 2.0% were prepared. The solution was ultrasonically degassed for 2 h and then set aside.
[0067] The degassed spinning solution was transferred to a 10mL needle tube, and a flat-head needle with an inner diameter of 0.40mm was used as the capillary for electrospinning. After the bubbles in the needle tube were exhausted, it was fixed horizontally on the slide, so that its axis was consistent with the center of the spinning receiving device, and the distance between the needle and the drum was adjusted to 15cm, the voltage was set to 14kV, the spinning solution flow rate was 0.8mL / h, and the drum with aluminum foil was used as the receiving device to prepare the electrospun fiber membrane. After that, the prepared electrospun nanofiber membrane was placed in a vacuum drying oven for 24h to completely evaporate the residual solvent.
[0068] 1.2 Determination of spinning solution properties
[0069] The viscosity of the spinning solution was measured using a rheometer, and a cone plate with a diameter of 40 mm and an angle of 1.59° was selected as the fixture. The shear rate was measured at 25°C for 1 s -1 The viscosity of the sample.
[0070] The conductivity was measured by a multi-parameter water quality analyzer. The analyzer was preheated 0.5 hours before the test and the test was performed after calibration with a standard potassium chloride solution.
[0071] Scanning electron microscope: Same as Example 1.
[0072] Fourier infrared spectroscopy analysis: A Fourier infrared spectroscopy scanner was used to analyze the effect of LAE addition on the chemical structure of the nanofiber membrane. Before the test, the LAE powder and the nanofiber membrane were dried at 50°C for 1 hour and then stored in a drying dish for use. The infrared absorption spectrum of the LAE powder was measured using potassium bromide dried at 105°C for 1 hour as the substrate, while the nanofiber membrane was measured using air as the blank control. The instrument resolution was set to 4 cm -1 , scan 32 times to obtain the sample at 400-4000cm -1 Absorption spectrum over a range of wavelengths.
[0073] Thermal performance analysis: A differential calorimeter was used to measure the thermodynamic properties of the samples. A certain amount of sample was sealed in an aluminum crucible, and the program heating rate was set to 10°C / min, and the temperature range was 20-200°C. In a nitrogen environment with a flow rate of 50mL / min, a heating-cooling cycle was performed to eliminate the thermal history of the material, and then a second heating was performed at the same rate to obtain the glass transition temperature T of the material. g , cold crystallization temperature T cc , melting temperature T m And crystallinity X c Among them, the crystallinity calculation formula is as follows:
[0074]
[0075] In the formula, ΔH m (J.g -1 ) refers to the melting enthalpy of the sample, ΔH cc (J.g -1 ) is the sample cold crystallization enthalpy, and The melting enthalpy of 100% PLA crystallization is 93.6 J·g -1 .
[0076] The thermal stability of the material was analyzed using a thermogravimetric analyzer. During the measurement, a certain amount of sample was placed at the bottom of an aluminum crucible, and the temperature was raised from 20°C to 600°C at a rate of 10°C / min in a 50mL / min nitrogen environment, and the weight loss curve of the material was recorded. All experiments in this section were repeated twice, and the results were analyzed using TA universal software.
[0077] Antimicrobial activity assay
[0078] 1) Microbial culture
[0079] The Gram-positive bacteria Staphylococcus aureus and the Gram-negative bacteria Escherichia coliO157:H7 were used as model microorganisms to evaluate the antibacterial properties of the film. The detoxified S.aureus (CGMCC 1.89) used in the test was purchased from the China General Microbiological Collection Center, and E.coli O157:H7 (NCTC 12900) was purchased from the National Culture Collection of the United Kingdom. Before the test, the first-generation bacteria stored at -80°C were thawed and streaked to obtain single colonies, which were sealed and placed in a 4°C refrigerator for later use. Pick a single colony and place it in 5mL of tryptone soy broth (TSB) and shake it at 37°C overnight. After 12 hours, the expanded culture solution was added to the fresh broth at a ratio of 1:100 and shaken in a shaker at 37°C / 220rpm until the absorbance at 600nm was 0.8 before use. At this time, the microbial concentration was about 8log 10 CFU / mL.
[0080] 2) Antibacterial test
[0081] The antibacterial activity of the film was qualitatively determined by the inhibition zone method. Before the test, the nanofiber membrane with a diameter of 6 mm was sterilized under ultraviolet for 2 hours. Use a sterile cotton swab to evenly apply the above bacterial solution on the surface of the tryptic soy agar (TSA) culture medium, then place the sample on the surface of the TSA culture medium and press gently to ensure that the sample is in full contact with the culture medium. After culturing at 37°C for 24 hours, the diameter of the inhibition zone was determined by the cross method. This test was repeated 6 times.
[0082] 3) Shake bottle method
[0083] The shake flask method was used to qualitatively determine the antibacterial activity of the nanofiber membrane. 6 CFU / mL was used as the indicator, and this test used it as the initial concentration to determine the antibacterial activity of the film. Before the test, pure PLA film and nanofiber membranes containing 0.5%, 1.0%, 1.5% and 2.0% LAE were cut into small pieces of 1cm×3cm, sterilized under UV for 2h, and then used. Subsequently, different samples were mixed with 5mL of an initial concentration of about 6log 10 CFU / mL bacterial solution was mixed and placed in 37℃ / 220rpm shaking culture for 12h. A pure bacterial solution group without any sample was set up as a blank control. After the culture was completed, 4mL of bacterial solution was aspirated into a sterile centrifuge tube, centrifuged at 4℃ / 8000rpm for 10min, and the supernatant was discarded. The bacteria were resuspended in 0.85% sterile saline, and this was repeated twice to remove the influence of the antibacterial agent. After the washed bacterial suspension was appropriately diluted, three appropriate gradient dilutions were selected for inverted plate operation. After the agar culture medium solidified, it was inverted and cultured at 37℃ for 24h and then counted. The results are expressed as log 10(N0 / N), where N0 is the initial viable cell number (CFU / mL) and N is the viable cell number after 12 h (CFU / mL).
[0084] 1.3 Statistical analysis
[0085] Except for those specially marked, the above experiments were repeated three times. The results were analyzed by SPSS18.0 for variance analysis and Duncan multiple comparisons, with a significant level of p < 0.05. All experimental results are expressed as "mean ± standard deviation".
[0086] 2 Results and analysis
[0087] 2.1 Spinning solution properties
[0088] Table 4 Physical properties of spinning solution and average diameter of nanofibers
[0089]
[0090]
[0091] Note: The same indicator marked with different lowercase letters indicates that there are significant differences among samples (p<0.05).
[0092] 2.2 Microstructure analysis of nanofiber membrane
[0093] SEM was used to characterize the effect of LAE addition on the microstructure of PLA nanofiber membrane. Figure 1 As shown. Under the experimental conditions, pure PLA nanofibers with an average diameter of 644±98nm can be prepared, and the fibers are smooth, uniform, and have no beaded morphology. After adding LAE, the diameter of the nanofibers decreased by 43.5%-49.5%, forming nanofibers with a diameter of 325nm-364nm (forming an active antibacterial film with a higher specific surface area), which may be related to the change in the conductive properties of the spinning solution caused by the addition of LAE. Figure 1 As can be seen from F, the nanofibers prepared by adding 0.5% LAE are the thinnest and most uniform.
[0094] 2.3 Fourier transform infrared spectroscopy analysis
[0095] The infrared spectra of LAE powder and LAE / PLA nanofiber membranes with different contents are shown in Figure 2 The appearance of amino and amide characteristic peaks in the nanofiber membrane PLA / LAE indicates that LAE is successfully incorporated into the nanofiber membrane. -1 The absorption peaks between 1650cm and 1650cm are related to the symmetric and asymmetric stretching vibrations of NH in the amino group. -1 The absorption peak at 1533 cm corresponds to the stretching vibration of C=O in the secondary amide group. -1The absorption peaks at 3328, 3171, 1650, and 1533 cm-1 are caused by the NN bending and NC stretching vibrations of the amide group. -1 The absorption peaks at all locations showed an increasing trend. However, the addition of LAE did not cause the characteristic peaks to shift, indicating that there was almost no chemical interaction between LAE and PLA.
[0096] 2.4 Thermal performance analysis
[0097] 2.4.1 Differential scanning calorimetry analysis
[0098] Table 5 DSC characteristic parameters of PLA and PLA / LAE electrospun membranes
[0099]
[0100] Note: The same indicator marked with different lowercase letters indicates that there are significant differences among samples (p<0.05).
[0101] 2.4.2 Thermogravimetric analysis
[0102] Figure 3 Thermogravimetric analysis curves and derivative thermogravimetric curves of nanofiber membranes before and after loading with LAE. Figure 3 B shows that pure PLA nanofiber membrane thermally degrades in one step. After adding LAE, the thermal degradation of nanofiber membrane is divided into two stages, which is particularly obvious in the PLA fiber membrane with 2.0% LAE added.
[0103] 2.5 Antimicrobial activity analysis
[0104] 2.5.1 Antibacterial test
[0105] The antibacterial activity of PLA / LAE nanofiber membrane against S. aureus and E. coli O157:H7 was qualitatively determined by the inhibition zone method. Figure 4. The diameter of the inhibition zone was determined by the cross method and is listed in Table 6. After 24 hours of culture, the pure PLA nanofiber membrane was covered with microorganisms, while after adding LAE, obvious inhibition zones appeared around the nanofiber membrane, indicating that the PLA / LAE nanofiber membrane had significant inhibitory activity against S. aureus and E. coli O157:H7 (p<0.05). As can be seen from Table 5, with the increase of LAE concentration, the diameter of the inhibition zone gradually increased. The diameter of the inhibition zone of nanofiber membranes containing different concentrations of LAE against E. coli O157:H7 was significantly different (p<0.05). When LAE is 2.0%, the diameter of the inhibition zone of the film can reach 10.54±0.32mm. PLA / LAE nanofiber membrane also showed the same antibacterial trend against S. aureus. As the LAE concentration increased, the diameter of the inhibition zone increased from 14.14 mm to 15.22 mm. However, there was no significant difference in the diameter of the inhibition zone produced by the nanofiber membrane with different concentrations of LAE on S. aureus (p>0.05).
[0106] Table 6 Inhibition zone diameters of PLA / LAE nanofiber membranes against S. aureus and E. coli O157:H7
[0107]
[0108] Note: Different lowercase letters under the same bacterial species indicate significant differences among samples (p<0.05).
[0109] Depend on Figure 4 It can be seen that S. aureus is more sensitive to PLA / LAE nanofiber membrane than E. coli O157:H7.
[0110] 2.5.2 Shake bottle method
[0111] To quantitatively characterize the antimicrobial activity of PLA / LAE, foodborne pathogens and antimicrobial films were co-cultured in TSB broth at 37°C for 12 h. Figure 5 After 12 hours, the growth rates of S. aureus and E. coli O157:H7 in both the untreated group and the pure PLA-treated group were about 3 log 10 CFU / mL, and there was no significant difference between the two treatments (p>0.05), indicating that pure PLA film had no antibacterial activity. However, after adding different concentrations of LAE, the antibacterial film showed significant antibacterial activity against both (p<0.05). Among them, only 0.5% LAE-PLA can inhibit the growth of S. aureus, and as the LAE concentration increases, the antibacterial efficiency of PLA / LAE nanofiber membrane gradually increases. Compared with the initial concentration, the nanofiber membrane containing 1.0% LAE can reduce S. aureus by 2.87log 10CFU / mL, and there was no significant difference in antibacterial activity with 1.5% LAE-PLA nanofiber membrane (p>0.05). However, 2.0% LAE-PLA nanofiber membrane could reduce S. aureus by 4.42 log 10 CFU / mL, showing good bactericidal activity.
[0112] The antibacterial activity of PLA / LAE nanofiber membrane against E.coli O157:H7 also showed the same trend, where 2.0% LAE-PLA could reduce it to below the detection limit after 12 hours, with a killing effect of 6.35 log 10 CFU / mL, which was superior to the killing effect against S. aureus.
[0113] Example 3: Effects of LAE-PLA nanofiber membrane combined with ultrahigh pressure treatment on common foodborne pathogens S. aureus and E. coli O157:H7
[0114] 1. Test methods
[0115] 1.1 Sample processing
[0116] The nanofiber membranes loaded with different concentrations of LAE were cut into 1 cm × 3 cm pieces and packaged in sterile sampling bags. Before the test, the samples were sterilized under ultraviolet light for 2 hours and then placed in high-temperature cooking bags. 8 -10 9 5 mL of S. aureus and E. coli O157:H7 bacterial suspensions (same as the bacterial suspensions in 1.2 of Example 2) with CFU / mL were dispensed into high-temperature cooking bags, and the bags were heat-sealed after the air on the top was removed. A group without PLA film was set as a blank control, and the killing effect of the film on microorganisms under normal pressure was used as a reference. At room temperature, the encapsulated samples were treated with FB-110G5 high-pressure equipment using water as the pressure transmission medium. Among them, S. aureus was treated at 100MPa, 200MPa, and 300MPa for 5 minutes, while E. coliO157:H7 was treated at 200MPa and 300MPa for 5 minutes.
[0117] 1.2 Microbial survival and sublethal cell assays
[0118] Take 4.5mL of sample and transfer it to a 10mL sterile centrifuge tube. Centrifuge at 4℃ / 8000rpm for 10min. Then wash the precipitate obtained by centrifugation twice with 0.85% saline and resuspend it. After the bacterial suspension is appropriately diluted, take 1mL of the appropriate gradient dilution solution and add it to a sterile culture dish. Pour 55℃ TSA medium and mix well. After the agar solidifies, invert and culture at 37℃ for 24h, and count the colonies.
[0119] The determination of sublethal damage to microorganisms is expressed by the difference in cell growth on a non-selective medium and a selective medium. TSA was used as a non-selective medium, and TSA medium supplemented with 6.5% NaCl and 1.0% NaCl were used as selective medium for S. aureus and E. coli O157:H7, respectively. Among them, the NaCl concentration used in the selective medium is the highest concentration that does not cause a significant decrease in untreated cells. Before the experiment, S. aureus and E. coli O157:H7 were cultured in TSA medium supplemented with different concentrations of NaCl to determine the specific amount of NaCl in the selective medium.
[0120] 1.3 Study on the synergistic mechanism of high pressure and antibacterial film on Staphylococcus aureus
[0121] By changing the treatment sequence of HPP and antibacterial film, the synergistic mechanism of 300MPa / 5min high-pressure treatment and antibacterial film was explored. In order to maintain the consistency of the action time under different treatment sequences, the time of the experimental process is now explained. The pressure rise time of the ultra-high pressure equipment used in this experiment is 7min, and the pressure holding time is 5min, so the normal pressure treatment group is placed for 12min. The co-action time of the antibacterial film migration liquid and S. aureus after HPP treatment is 27min, because the high-pressure treatment time is 12min, and the time from the completion of the treatment to the centrifugal treatment is 15min, that is, the contact time between the bacterial suspension and the antibacterial film migration liquid is 27min. This section sets up the following four groups of experiments. Before the experiment, the concentration is about 8log 10 The CFU / mL bacterial solution was centrifuged at 4°C to collect the bacteria, and the obtained bacteria were washed once and resuspended in 0.85% saline for later use.
[0122] 1.3.1 Bactericidal effect of antibacterial films of different concentrations on HPP-treated S. aureus at normal pressure
[0123] The sample treatment method is the same as that in Example 3, step 1.1, 5 mL of S. aureus bacterial solution resuspended in 0.85% saline was dispensed into high temperature cooking bags containing LAE antibacterial films of different concentrations, and the bags were heat sealed after the air on the top was removed. The packaged samples were left to stand at normal pressure for 12 minutes.
[0124] 1.3.2 Bactericidal effect of antimicrobial film migration liquid on HPP-treated S. aureus at normal pressure
[0125] Take 5mL of S. aureus bacterial solution resuspended in 0.85% saline and divide it into high-temperature cooking bags, heat seal it, and place it under 300MPa high pressure for 5min. After the treatment is completed, take 4mL of the treated bacterial solution and centrifuge it at 4℃ / 8000rpm for use. At the same time, divide the antibacterial film (1cm×3cm) containing different concentrations of LAE into high-temperature cooking bags, add 5mL of saline, heat seal it, and place it at normal pressure for 12min. Take 4mL of different antibacterial film migration liquids under normal pressure and add them to the above precipitate, mix them evenly and place them at room temperature for 27min.
[0126] 1.3.3 Bactericidal effect of antibacterial film migration liquid under ultrahigh pressure on HPP-treated S. aureus
[0127] The treatment method of S. aureus bacterial suspension is the same as that in 1.3.2 above. The bacterial suspension obtained by centrifugation is resuspended in the migration solution of different antibacterial films after HPP (300MPa / 5min) treatment, mixed evenly and placed at room temperature for 27 minutes.
[0128] 1.3.4 Sterilization effect of antibacterial films of different concentrations on S. aureus under ultrahigh pressure
[0129] The sample treatment method is the same as 1.3.1, and the packaged sample is pressure treated at 300MPa for 5 minutes.
[0130] The bacterial solution after the above four groups of experimental treatments was centrifuged at 8000rpm for 10min to collect the precipitate, and the precipitate was washed twice with 0.85% saline to eliminate the inhibitory effect of residual LAE on microorganisms. The survival of S. aureus under different treatments was determined by plate counting method.
[0131] 1.4 Effect of high pressure and antibacterial film on the preservation of coconut water
[0132] Select mature, fresh and undamaged coconuts to collect coconut water, filter it through eight layers of gauze, and place it in a measuring cup for later use. According to the results of previous tests, high pressure can reduce S. aureus and E. coli O157:H7 by 5 log 10CFU / mL or more 2.0% LAE-PLA antibacterial film was used for subsequent test operation. Pure PLA film group, 300MPa / 5min high pressure treatment group, 500MPa / 5min high pressure treatment group, 2.0% LAE-PLA film treatment group and 300MPa / 5min high pressure and 2.0% LAE-PLA combined treatment group were set up for coconut water preservation test. The nanofiber membrane was cut into 2cm×3cm small pieces and added to the sterile sampling bag and sterilized under ultraviolet light for later use. 10mL coconut water was added to the high-temperature cooking bag containing 0% LAE-PLA and 2.0% LAE-PLA antibacterial film, respectively, and the top air was removed and heat-sealed, and different pressure treatments were performed. The treated samples were refrigerated at 4℃ and sampled at 0, 3, 7, 14, 21, 28, 35, 42, and 49 days. The total colony count and mold and yeast were determined using plate count agar and red Bengal medium, respectively. The former was incubated inverted at 37°C for 48 h, and the latter was incubated at 28°C for 72 h.
[0133] 1.5 Statistical analysis
[0134] SPSS18.0 was used for variance analysis and Duncan multiple comparison, with a significance level of p < 0.05. The test results were expressed as "mean ± standard deviation".
[0135] 2 Results and discussion
[0136] 2.1 Killing effect of ultrahigh pressure and antibacterial film on pathogenic bacteria
[0137] The killing effect of ultra-high pressure combined with antibacterial film on common food-borne pathogens. The results are as follows Figure 6 At normal pressure, S. aureus is very sensitive to LAE, and only 0.5% LAE-PLA treatment can reduce its 10 CFU / mL, and with the increase of antimicrobial agent concentration, the bactericidal effect of the antimicrobial film gradually increased, among which 2.0% LAE-PLA could reduce S. aureus by 5.58 log 10 CFU / mL. However, as a Gram-positive bacterium, S. aureus has a certain pressure resistance, and 300MPa / 5min only reduces it by about 1 logarithm. The combination of HPP and antibacterial film can significantly improve the inactivation rate of S. aureus, and show an obvious synergistic bactericidal effect. Only 200MPa high pressure combined with 2.0% LAE-PLA can reduce S. aureus to below the detection limit.
[0138] The bactericidal effect of the antibacterial film on E.coli O157:H7 under normal pressure has the same trend as that of S.aureus. Compared with the latter, E.coli O157:H7 is less sensitive to the antibacterial film, and 2% LAE-PLA can only reduce its sensitivity by 1.78log 10 CFU / mL. Figure 6 B shows that high pressure treatment at 300 MPa / 5 min can reduce the concentration of E. coli O157:H7 by 6.17 log 10 CFU / mL. However, the combined treatment of ultrahigh pressure and antibacterial film did not show a synergistic bactericidal effect on E.coli O157:H7. After treatment at 200MPa and 300MPa, it was found that the antibacterial film treatment weakened the killing effect of ultrahigh pressure on E.coli O157:H7, among which E.coli O157:H7 treated with 0.5% LAE-PLA was the most significant (p<0.05). However, as the LAE concentration increased, the weakening effect of high pressure decreased. Although the antibacterial film weakened the ultrahigh pressure sterilization effect, the combined effect of 2.0% LAE-PLA and 300MPa / 5min high pressure can still reduce E.coli O157:H7 by 5.34log 10 CFU / mL, which meets the industrial processing requirement of reducing the relevant pathogens in fruit and vegetable juice by five logarithms. In view of the fact that the combined treatment of 300MPa ultrahigh pressure and antibacterial film can reduce S. aureus to below the detection limit and reduce E. coli O157:H7 by more than five logarithms at a relatively low pressure, it is believed that it can be used as an effective processing method for subsequent experiments.
[0139] 2.2 Effect of ultrahigh pressure combined with antibacterial film on sublethal damage to bacteria
[0140] Depend on Figure 7 It can be seen that high pressure of 200MPa and below did not show bactericidal activity against S. aureus, and only some antibacterial film treatment groups showed sublethal damage. However, after high pressure treatment at 300MPa, the growth of S. aureus in the control group and the pure PLA treatment group on selective and non-selective culture media showed significant differences (p<0.05). Among them, the sublethal bacteria in the control group were as high as 1.49log 10 After combined treatment with antibacterial film, no sublethal bacteria appeared in each treatment group, indicating that antibacterial film can be used as a good barrier technology to improve the safety of ultra-high pressure food.
[0141] 2.3 Study on the synergistic bactericidal mechanism of high pressure and antibacterial film on S. aureus
[0142] By controlling the order of high pressure and film action, four groups of tests were set up for verification, namely: the killing effect of antibacterial film on S. aureus under normal pressure, the killing effect of antibacterial film effluent under normal pressure on S. aureus after ultra-high pressure treatment, the killing effect of antibacterial film effluent under ultra-high pressure on S. aureus after HPP treatment, and the killing effect of ultra-high pressure and antibacterial film simultaneous treatment on S. aureus. The results are as follows Figure 8 shown.
[0143] Among all antibacterial film treatment groups, the inactivation efficiency of S. aureus by ultrahigh pressure and antibacterial film treatment simultaneously was significantly better than that by acting on microorganisms in sequence (p<0.05), indicating that ultrahigh pressure and LAE have synergistic bactericidal activity. This may be because high pressure treatment causes reversible damage to the bacterial cell membrane, and the cell membrane damage is repaired after pressure relief, which reduces the sensitivity to LAE. Therefore, the inactivation efficiency of S. aureus by ultrahigh pressure and antibacterial film in sequence is lower than that by acting simultaneously.
[0144] 2.4 Preservation effect of high pressure combined with antibacterial film on coconut water
[0145] In order to further explore the feasibility of combined treatment of ultra-high pressure and antibacterial film in food, low-acid coconut water was selected as the test object to determine the effects of different pressures and antibacterial films on the total number of colonies and the growth of mold and yeast during storage. The results are as follows: Fig. 9 The initial total colony count in coconut water was 1.12 log 10 CFU / mL, the initial colony count can be reduced by 0.60-1.12log after ultrahigh pressure and 2.0% LAE-PLA film treatment 10 CFU / mL. The total number of colonies in the control group increased linearly during storage, reaching a concentration of 6.32 log on day 14. 10 CFU / mL. All treatment groups were in the lag phase within 14 days, indicating that these treatments can effectively inhibit the growth of natural flora in coconut water. After 14 days, bacteria in some treatment groups resumed growth, among which the microorganisms recovered fastest after 300MPa / 5min treatment, and the total colony count reached about 4log at 21 days. 10 CFU / mL, indicating that 300MPa / 5min treatment alone is not enough to maintain the microbial stability of coconut water during storage. It is reported that 500MPa / 5min treatment can effectively inhibit the total number of colonies in coconut water, and is lower than thermal sterilization (72℃, 15s) during 30d storage, with good storage effect. Therefore, 500MPa / 5min is used as the positive control of ultra-high pressure processing in this section. The study found that the microorganisms in the 500MPa / 5min treatment group also resumed growth after 14d, and reached 2.19log at 49d. 10CFU / mL, which was not significantly different from the 2.0% LAE-PLA treatment group (p>0.05). However, after the combined action of 2.0% LAE-PLA and 300MPa / 5min high pressure, the microorganisms in coconut water remained stable, and the microbial content was still below the detection limit until the end of storage, indicating that the combined action of ultra-high pressure and antibacterial film can effectively inhibit the recovery growth of microorganisms in low-acid coconut water, and has a good preservation effect. According to the provisions of GB 7101-2015 "National Food Safety Standard Beverages", the total colony count, mold and yeast in fruit and vegetable juice beverages should be less than 2, 1.3, and 1.3 log, respectively. 10 CFU / mL. As of 49 days of storage, only 300MPa / 5min ultrahigh pressure treatment combined with 2.0% LAE-PLA could maintain the storage stability of coconut water.
[0146] Depend on Fig. 9 B shows that the initial concentration of mold yeast in coconut water is only 0.06log 10 CFU / mL, no recovery of mold and yeast was found in all treatment groups during storage. Compared with bacteria, eukaryotic microorganisms such as mold and yeast are more sensitive to HPP, so their growth can be completely inhibited at a lower intensity. The control group basically showed an upward trend, and mold and yeast could reach 3log after 49 days. 10 In summary, the combined treatment of 300 MPa / 5 min and 2.0% LAE-PLA antimicrobial film can completely inhibit the growth of microorganisms during 49 days of storage, indicating that it can be used as an energy-saving processing method that can maintain the stability of microorganisms in low-acid juice.
[0147] In summary, the present invention studies the killing effect of high pressure combined with antibacterial film on S. aureus and E. coli O157: H7 and its application feasibility in low-acid coconut water. The effects of combined treatment on microbial growth and storage stability of coconut water are determined by colony count, sublethal cell assay and other methods. The main results are as follows:
[0148] (1) HPP and PLA / LAE antimicrobial films have a synergistic bactericidal effect on S. aureus. Only 200 MPa high pressure and 2% LAE-PLA can reduce the microorganisms to below the detection limit, but only 300 MPa / 5 min combined with 2.0% LAE-PLA can reduce E. coli O157:H7 by more than 5 logarithms. In view of the industry's requirements for the bactericidal intensity of fruit and vegetable juice processing technology, subsequent research was conducted at 300 MPa / 5 min.
[0149] (2) Under 300MPa / 5min treatment, the sublethal damage to S. aureus cells can reach 1.49log 10CFU / mL, and the combined treatment with antibacterial film can eliminate sublethal damaged cells, thus effectively improving the safety of ultra-high pressure food. However, E. coli O157:H7 did not show sublethal damage under the measured pressure.
[0150] (3) By controlling the order of different treatment methods and conducting migration tests, it was verified that the synergistic bactericidal effect of UHP combined with PLA / LAE antibacterial film on S. aureus was not caused by the increase in the amount of LAE migration, but may be due to the change in the permeability of the bacterial cell membrane of S. aureus caused by UHP, making it more sensitive to the antibacterial film treatment, thus showing a synergistic killing effect.
[0151] (4) During the storage of coconut water, except for the 300MPa / 5min combined with 2.0% LAE-PLA treatment group, the other treatment groups all showed the phenomenon of microbial recovery growth. The total colony count of coconut water treated with 500MPa / 5min reached 2.19log10 CFU / mL at 49 days. No live bacteria were detected in the combined treatment group, indicating that the combined treatment of ultrahigh pressure and antibacterial film has a good preservation effect on low-acid juice, and the combined treatment of the two can reduce the ultrahigh pressure processing intensity from 500MPa / 5min to 300MPa / 5min, effectively saving energy and reducing the loss of high-pressure equipment.
Claims
1. A method for sterilizing by combining lauroyl arginine ethyl ester hydrochloride antibacterial nanofiber membrane with ultrahigh pressure, comprising the following steps: mixing the lauroyl arginine ethyl ester hydrochloride antibacterial nanofiber membrane with a sample to be sterilized, and treating the mixture under a pressure of 200-300 MPa for 5 min at room temperature; The method for preparing the lauroyl arginine ethyl ester hydrochloride antibacterial nanofiber membrane comprises the following steps: 1) Dissolve lauroyl arginine ethyl ester hydrochloride powder in N, N-dimethylformamide, mix it with chloroform in a ratio of 1:9 (v / v), add polylactic acid masterbatch, stir at room temperature until completely dissolved, and prepare a spinning solution with a mass concentration of lauroyl arginine ethyl ester hydrochloride of 0.5%-2.0%, and ultrasonically degas for standby use; 2) electrospinning the degassed spinning solution to obtain an electrospun nanofiber membrane, which is then placed in a vacuum drying oven for drying to completely volatilize the residual solvent, thereby obtaining the lauroyl arginine ethyl ester hydrochloride antibacterial nanofiber membrane; In the step 1), the mass concentration of the polylactic acid masterbatch in the spinning solution is 6%-10%; In the step 2), the process conditions of the electrospinning are as follows: the distance between the needle and the drum is adjusted to 15 cm, the voltage is set to 10-16 kV, and the spinning solution flow rate is 0.6-1.0 mL / h; The sample to be sterilized is liquid.
2. The method according to claim 1, Features: The lauroyl arginine ethyl ester hydrochloride antibacterial nanofiber membrane needs to be placed under ultraviolet light for sterilization before use.
3. The method according to claim 1 or 2, Features: The lauroyl arginine ethyl ester hydrochloride antibacterial nanofiber membrane is mixed with the sample to be sterilized in a high-temperature cooking bag, and after mixing, the top air is removed and the bag is heat-sealed.
4. The method according to claim 1 or 2, Features: The method can kill Gram-positive bacteria and / or Gram-negative bacteria.
5. The method according to claim 1, Features: In the step 1), the mass concentration of the polylactic acid masterbatch in the spinning solution is 8%; In the step 1), the mass concentration of lauroyl arginine ethyl ester hydrochloride in the spinning solution is specifically 0.5%, 1.0%, 1.5% or 2.0%; In the step 2), the process conditions of the electrospinning are as follows: the distance between the needle and the drum is adjusted to 15 cm, the voltage is set to 14 kV, and the spinning solution flow rate is 0.8 mL / h.
